Early and long-term effects of prophylactic and post-excision human papillomavirus vaccination on recurrent high-grade cervical intraepithelial neoplasia relative to margin status: a retrospective cohort study in the Czech Republic - Petráš, Marek; Lomozová, Danuše; Dvořák, Vladimír; Dvořák, Vladimír; Malinová, Jana; Trnková, Markéta; Fišer, Ivan; Dlouhý, Pavel; Rosina, Jozef; Lesná, Ivana Králová (The Lancet regional health. Europe, 2025)
BACKGROUND: The effect of human papillomavirus (HPV) vaccination on cervical intraepithelial neoplasia grade 2 or worse (CIN2+) recurrence with respect to cone margin positivity is unknown. Most studies assessed this effect beyond two months post-conisation. We aimed to determine both the duration and early onset of effect in women who had been prophylactically vaccinated or vaccinated after conisation, considering cone margin status. METHODS: This cohort study used data from one of the central laboratories in the Czech Republic, covering approximately 33% of women undergoing national cervical cancer screening. It included women treated for CIN2+ between 2010 and 2024 who had received either prophylactic HPV vaccination (available through the national immunisation program since 2011) or post-conisation vaccination (recommended by the Czech Gynaecological and Obstetrical Society since 2008). The vaccination effect was estimated using the incidence rate ratio (IRR) from a Poisson regression model, calculated as 100 × (1-IRR). FINDINGS: Of the 10,054 women enrolled, 919 were vaccinated after conisation, 502 prophylactically, and 169 had undetermined timing of vaccination. Throughout the follow-up period, CIN2+ recurrence was observed in 513 unvaccinated women, with a rate of 14·61 per 1000 person-years (py), in 14 prophylactically vaccinated women, with a rate of 5·84 (54% reduction; 95% confidence interval [CI]: 22-73%), and in 15 women vaccinated post-excision, with a rate of 3·37 (74% reduction; 95% CI: 57-85%). The high recurrence rate of 58·59 per 1000 py within six months of conisation was reduced by 80% (95% CI: 19-95%) with prophylactic vaccination and by 89% (95% CI: 57-97%) with incomplete post-excision vaccination. Among a total of 1771 women with a positive cone margin, recurrence was identified in 272 of 1568 unvaccinated women, corresponding to a recurrence rate of 51·62 per 1000 py. A reduction was observed in 84 prophylactically vaccinated and in 119 women vaccinated post-excision, with only 6 recurrence cases documented in each group. This corresponded to recurrence rates of 14·94 (62% reduction; 95% CI: 14-83%) and 9·78 per 1000 py (79% reduction; 95% CI: 52-90%), respectively. INTERPRETATION: Regardless of timing, HPV vaccination has a beneficial long-term effect in lowering the risk of CIN2+ recurrence. Despite the greater reduction in relapse achieved by post-excision vaccination, the difference compared with the prophylactic one was not statistically significant. The most pronounced benefit was observed within the first six months post-conisation, particularly in women with a positive cone margin. FUNDING: Cooperatio 31 fund, Health Sciences, Charles University, Prague, Czech Republic.
Keywords: Adjuvant intervention; Recurrence; Vaccination; Conisation; Human papillomavirus; Cervical intraepithelial neoplasia